MOLECULAR MECHANISMS INVOLVED IN ENDOPLASMIC RETICULIM STRESS DEVELOPMENT - WHAT DO WE KNOW UP TODAY - Vidičević Novaković, Sašenka (Medicinski podmladak, 2023)
Endoplasmic reticulum (ER) is an intracellular organelle involved in protein synthesis and folding. When balance between cell needs for proteins and ER capacity to fold proteins is disrupted, nonfunctional, unfolded or misfolded proteins are accumulated in ER lumen, leading to endoplasmic reticulum stress (ER stress). One of the ways cell uses to overcome ER stress is unfolded protein response (UPR) activation. UPR is initiated by the activation of three ER transmembrane proteins. These proteins are IRE-1α (inositol requiring enzyme-1α), PERK (protein kinase RNA-like endoplasmic reticulum kinase) i ATF6 (activating transcription factor 6) and they are activated when ER chaperone, GRP78 releases their intraluminal domains. Activation of these transmembrane sensor starts mechanisms that should restore ER function. If ER function is not restored and balance is not achieved, apoptosis is induced in order to maintain cell homeostasis. Activated IRE-1α leads to XBP-1 (X-box binding protein-1) mRNA splicing and activates MAP kinases and inflammatory pathways that involve NFƙB. Activated ATF 6 (ATF6f) functions as a transcriptional factor and increases gene expression for XBP-1, while PERK activation leads to phosphorylation and inactivation of eukaryotic initiation factor 2 (eIF2α) which further leads to decreased protein synthesis. eIF2α phosphorylation also leads to selective synthesis of ATF4, transcriptional that in irreversible damaged cells induces cell death activation by CCAAT-enhancer binding protein homologous protein (CHOP) transcription.It is known that ER stress and UPR have a role in different diseases pathogenesis such as diabetes, inflammation, tumors and neurodegenerative diseases. Knowing signaling pathways of UPR and mechanisms by which UPR is involved in diseases pathogenesis can be very significant in targeted therapeutic approaches development.
Keywords: ER stress; UPR; IRE-1α; PERK; ARF6